Una Mirada Sobre la Negociación Colectiva en América Latina - Rosenbaum Rimolo, Jorge (2016)
The author analyzes the current status of freedom of association in Latin America, specifically collective bargaining and the different schemes this institution presents itself after the neoliberal policies of economic deregulation took place in the decade of nineteen ninety.